Technological and probiotic role of adjunct cultures of non-starter lactobacilli in soft cheeses - Burns, Patricia Graciela (2012)
The influence of two cheese-isolated Lactobacillus strains on cheese composition, acceptability and probiotic capacity was assessed. Soft cheeses with and without the addition of Lactobacillus plantarum I91 or Lactobacillus paracasei I90 were prepared. Gross composition was assessed and secondary proteolysis was described by soluble fractions and free amino acids profiles. Acceptability was determined by a panel of 98 non-trained consumers. Cheeses harboring added Lactobacillus strains were also studied invivo to evaluate their probiotic capacity. Gross composition of the cheeses was similar for control and treated (Lactobacillus-added) cheeses. Peptidolysis increased in cheeses with added lactobacilli, which was evidenced by a higher free amino acid content. Overall, the acceptability of the cheeses was good: 65%-80% of the consumers said that they " liked very much" or " liked" the cheeses. Cheeses with L.plantarum I91 showed the highest changes in composition and proteolysis and were the most accepted ones. On the contrary, composition of cheeses with L.paracasei I90 was similar to that of the controls, but these samples were less accepted than cheeses without lactobacilli. The oral administration of cheese containing L.plantarum I91 or L.paracasei I90 proved to be safe and able to enhance the number of IgA+cells in the small intestine lamina propria of mice. The use of selected strains of NSLAB exerted a technological and probiotic role: it contributed to the standardization of cheese quality and induced benefic health effects at the gut mucosa invivo. © 2011 Elsevier Ltd.